2022
DOI: 10.1002/agj2.20971
|View full text |Cite
|
Sign up to set email alerts
|

Paris polyphylla var. yunnanensis genotype classification and fluorescence visual identification

Abstract: Paris polyphylla Smith. var. yunnanensis (Franch.) Hand.-Mazz (PPY) is the legal species of Rhizoma Paridis recorded in the Chinese pharmacopeia. Therefore, accurate and convenient identification of PPY and its adulterants is key to the quality control of Rhizoma Paridis. In this research, according to single nucleotide polymorphism of internal transcribed spacer, two genotypes (YN-I and YN-II) of PPY are in existence. To avoid false-negative results from the omission of the genotype during authenticity ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Yin et al. (2022) reported that identification of Paris polyphylla variety yunnanensis and its adulterants is the key to the quality control of Rhizoma Paridis and visual fluorescent identification can be successfully used to discern two genotypes of Paris polyphylla variety yunnanensis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin et al. (2022) reported that identification of Paris polyphylla variety yunnanensis and its adulterants is the key to the quality control of Rhizoma Paridis and visual fluorescent identification can be successfully used to discern two genotypes of Paris polyphylla variety yunnanensis .…”
Section: Resultsmentioning
confidence: 99%
“…Another paper related to the root bacterial community showed that microbial taxa could be integrated into the management strategy of wheat stripe rust . Yin et al (2022) reported that identification of Paris polyphylla variety yunnanensis and its adulterants is the key to the quality control of Rhizoma Paridis and visual fluorescent identification can be successfully used to discern two genotypes of Paris polyphylla variety yunnanensis. studied the relationship between NAC062 and NAC103 (recognized as one of the largest specific transcription factor families in plants) and they stated that it is beneficial to understand their function in biotic and abiotic plant stress in order to improve plants tolerance under environmental stresses.…”
Section: Use and Roles Of Microorganisms In Agricultural Productionmentioning
confidence: 99%